Inferences about the coefficient of correlation in the standard bivariate normal distribution - Rosa, G. J. M. [UNESP]; Gianola, D. (My University, 2001)
The study of the association between two random variables that have a joint normal distribution is of interest in applied statistics; for example, in statistical genetics. This article, targeted to applied statisticians, addresses inferences about the coefficient of correlation (ρ) in the bivariate normal and standard bivariate normal distributions using likelihood, frequentist, and Baycsian perspectives. Some results are surprising. For instance, the maximum likelihood estimator and the posterior distribution of ρ in the standard bivariate normal distribution do not follow directly from results for a general bivariate normal distribution. An example employing bootstrap and rejection sampling procedures is used to illustrate some of the peculiarities.
Keywords: Bayesian inference; Bootstrap; EM algorithm; Maximum likelihood; Monte Carlo; Reference prior; Rejection sampling